Burhani Epistemological Order as a Scientific Construction of Islamic Education - Pranajaya, Syatria Adymas; Yunus, Firdaus M; Ikhwan, Muhammad; Syarifaturrahmatullah; Alfiyanto, Afif (Darul Ilmi Bina Insan Foundation, 2023)
In the realm of Islamic science, al-Jabiri's significant perspective on epistemology, outlined in